P-198 An analysis of the size of micro pronucleus in 2.1 pronuclear zygotes by using time-lapse images. (30th June 2022) - Nakajima, N; Kawano, H; Takai, A; Iimura, Y; Mutsumi, A; Azusa, O; Chen, M; Yamashita, N
Abstract: Study question: Is it possible to determine the difference between 2.1 pronuclear (2.1PN) zygotes and tripronuclear (3PN) zygotes from time-lapse images? Summary answer: A pronucleus of less than 15 μm in diameter can be considered the micro pronucleus (micro PN), and it is possible to classify 2.1PN zygotes. What is known already: 2.1PN zygotes are defined as zygotes with two pronuclei and one smaller pronucleus. Capalbo et al. (2017) reported that most of the 2.1PN-derived blastocysts were diploid by preimplantation genetic testing for aneuploidy (PGT-A), including single-nucleotide polymorphisms (SNPs) analysis. Thus, the treatment with 2.1 PN zygotes should be performed with chromosome testing. In Japan, where PGT-A is not available in principle, 2.1PN zygotes are rarely used in the embryo transfer. On the other hand, the size of the micro pronucleus in 2.1PN zygotes has not been clearly defined, and it is difficult to determine differences between 2.1PN and 3PN zygotes. Study design, size, duration: The study was performed retrospectively on 2463 cycles of in vitro fertilization (IVF) conducted at our clinic between August 2020 and December 2021. A total of 3073 embryos underwent conventional-IVF (c-IVF) or intracytoplasmic sperm injection (ICSI) and were cultured in the time-lapse incubator, of which 221 zygotes with three pronuclei were used in the study. Participants/materials, setting, methods: The diameter of the three PNs at one hour before syngamy from time-lapse images; 2.1 PN and 3PN zygotes were classified in the report by Capalbo et al . (2017). The age of the patients and the method of insemination between the groups were compared, and the diameter of the micro PN was analysed. Moreover, logistic regression analysis was performed to investigate the predictor of 2.1PN zygotes from the morphological characteristics of oocytes at ICSI. Main results and the role of chance: The mean age of each patient was 42.9 years for 2.1PN zygotes and 39.8 years for 3PN zygotes, significantly higher for 2.1PN zygotes ( P =0.003). On the other hand, when comparing the stage of oocyte maturation at the time of oocyte retrieval, there was no significant difference ( P =0.749). According to the insemination method, the incidence of 2.1PN zygotes was significantly higher in ICSI (including rescue-ICSI) compared to c-IVF: 32.9% [95%CI: 22.5-44.6%] vs 2.4% [95%CI: 0.1-12.9%] ( P <0.001). In terms of ICSI-derived zygotes, the mean age was also significantly higher for 2.1PN zygotes compared to 3PN zygotes: 43.3 years vs. 40.9 years ( P =0.03). The diameter of micro PNs calculated using the receiver operating characteristics (ROC) curve from the measurements of the diameter was less than 15 μm (AUC [95%CI]: AUC=0.988 [0.975-1.00]). Logistic regression analysis using age, position of the oocyte spindle at ICSI, cytoplasmic viscosity, and condition of the cell membrane as explanatory variables revealed a significant difference only in age ( P =0.0154, odds ratio [95%CI]: 1.18 [1.03-1.35]) and no statistically significant oocyte morphological characteristics. Limitations, reasons for caution: In this study, we have not investigated whether 2.1 PN zygotes become blastocysts. It will be necessary to further examine the criteria for 2.1PN along with chromosome testing to investigate the use of 2.1PN-derived blastocysts. Wider implications of the findings: A pronucleus of less than 15 μm in diameter can be considered a micro PN. Compared to 3PN zygotes, 2.1PN zygotes were more frequently observed in older patients and in ICSI-derived zygotes. However, it is difficult to predict the incidence of 2.1PN zygotes from the oocytes' morphological characteristics at ICSI. Trial registration number: not applicable